Correlation of clinical radiological features with histopathology and IHC to predict aggressive be-haviour of soft tissue sarcomas - Mandava Sumanth; Goginenu Tarun Chowdary; T Jaya Chandra; Sriram Burugupalli (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2022)
Introduction: A study was taken to assess the pathological predictors of aggressive behaviour ofsoft tissue sarcomas (STSs) and also to the correlation of STSs with clinical, radiological ofhistopathological techniques.Materials and methods: This was a prospective conducted fromJanuary 2016 to June 2017. All those coming to this institute with oral and oropharyngeal squamouscell cancers (SCCs) included. Smokers, tobacco chewers were not considered. Punch biopsy andsurgical biopsy were taken, respectively from inoperable and operable cases, paraffin blocks wereprepared. Tissue microarray (TMA) were constructed using these blocks. Tissue inhibitor ofmetalloproteinases 1 (TIMP 1) stain-ing was assessed on the cell membrane and cytoplasm of thetumour cells (TCs). Two areas that showed high-density stained cells were selected, several stainedTCs was counted. The intensity of staining was classified as negative, weak, moderate and strong.AXL kinase staining was scored as 0, 1+, 2+, and 3+. Eps8 staining was ranged from negative (0),to strong and diffuse (3+). P less than 0.05 was considered statistically significant.Results: A totalof 30 (100%) partic-ipants were included. With TIMP 1 expression, in normal mucosa, 63.3% (19)specimens did not stain; statistically, there was a significant difference. Around 53.3% (16) ofnormal mucosa did not stain with EPS8; statistically, there was a significant difference. In thesamples of SCC, 60% (18) showed 3+ sting and 40% (12) showed 2+. Statistically, there was asignificant difference.Conclusion: The expression of TIMP1, EPS8 and AXL establish their role inthe pathogenesis of oral and oropharyngeal SCCs